La construcción de la subjetividad en Doquier de Angélica Gorodischer - Luque, Cecilia Inés (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2011)
The inner monologue of the narrator works as an autobiographical discourse that constructs a singular identity image. In order to account for the constitutive processes of the subjectivity of this character, the links between the autós and the bios of that discourse are analyzed, also the links between the autós and the grapho, and the traces of the dialogue with the Other. The resulting self-image is that of a subjectivity whose eccentricity is marked by its distance with respect to two ideological paradigms which were at the time a measure of intelligibility of the person: the Catholic moral and sexual difference as defined by heterosexist thougth. That subjectivity is also marked by the dialogical relations with others, which destabilize and re-articulate previous self-images of the narrator character. The characteristics of the narrator’s subjectivity replace the modern notion of subject by the category of social agent: an entity not homogeneous but multiple, contradictory and contingent, always susceptible to change. Thus, the novel poses the challenge of thinking the subject in different terms from those of our automated patterns of intelligibility.